Domestic and Foreign Mutual Funds in Mexico : Do They Behave Differently? - Xiao, Jasmine (IMF Working Papers; Working Paper, 2015)
This paper utilizes a new dataset of foreign and domestic mutual funds in Mexico to assess their behavior and obtains three new findings. First, foreign mutual funds are more sensitive to global financial conditions and engage more in herding and positive feedback trading than domestic mutual funds, notably during episodes of market stress. Second, the behavior of foreign funds differs substantially across types of funds: bond funds are more sensitive to global factors and engage more in positive feedback trading than equity funds; funds sold to retail investors, open-end funds, small funds, and regional funds also appear to be less stable sources of capital flows. Third, there is indicative evidence that foreign funds' trading behavior is associated with higher local market volatilities, notably in periods of market stress; however, domestic mutual fund investors played some mitigating role.